Activated polyallene as versatile substrate for efficient preparation of fluorinated composite. (November 2022) - Yuan, Zongqian; Xu, Binbin; Jin, Weize; Huang, Xiaoyu; Zhang, Sen; Guo, Hao
Abstract: Introduction of fluorine into composites has been a subject of intense research because it brings about significant improvements in the performance of the composites. In particular, fluorine-containing composites exhibit excellent thermal stability, good chemical stability and low surface energy. However, the design of fluorine-containing composites is limited by the current polymerization and modification techniques. Herein, a series of double-bond-containing poly(phenoxyallene) (PPOA) polymers with tunable structure were facilely prepared through reversible addition-fragmentation chain transfer (RAFT) polymerization. To identify the RAFT polymerization conditions, RAFT homopolymerization of phenoxyallene (POA) was firstly conducted as a typical reaction. The effects of chain transfer agent (CTA), substituent of POA, temperature, and solvent were systematically investigated. Notably, highly efficient thiol-ene click reaction can be used for the direct modification of PPOA without further polymeric functionality transformation. When fluorinated thiol was used as reactant, a functional fluorine-containing polymer could be simply achieved, demonstrating the highly efficient efficiency of the postpolymerization modification. Considering the simple RAFT polymerization condition and excellent reactivity of double bonds in polymer structure, this thiol-ene postpolymerization modification might be a versatile platform for the precise fabrication of a broad variety of functional composites, especially for fluorine-containing composites. Graphical abstract: Image 1 Highlights: A versatile platform for the fabrication of a variety of functional composites. Excellent reactivity of double bonds in the poly(phenoxyallene) backbone. Highly efficient thiol-ene reaction for direct modification of poly(phenoxyallene) without functionality transformation.